Effect of the Protonation Degree of a Self-Assembled Monolayer on the Immobilization Dynamics of a [NiFe] Hydrogenase - Utesch, Tillmann (2012)
Understanding the interaction and immobilization of [NiFe] hydrogenases on functionalized surfaces is important in the field of biotechnology and, in particular, for the development of biofuel cells. In this study, we investigated the adsorption behavior of the standard [NiFe] hydrogenase of Desulfovibrio gigas on amino-terminated alkanethiol self-assembled monolayers (SAMs) with different levels of protonation. Classical all-atom molecular dynamics (MD) simulations revealed a strong correlation between the adsorption behavior and the level of ionization of the chemically modified electrode surface. While the hydrogenase undergoes a weak but stable initial adsorption process on SAMs with a low degree of protonation, a stronger immobilization is observable on highly ionized SAMs, affecting protein reorientation and conformation. These results were validated by complementary surface-enhanced infrared absorption (SEIRA) measurements on the comparable [NiFe] standard hydrogenases from Desulfovibrio vulgaris Miyazaki F and allowed in this way for a detailed insight into the adsorption mechanism at the atomic level.